Unlocking The Efficacy of Tetrahydrobiopterin (BH4) Towards Metabolic Profile and Growth Status in Children with Phenylketonuria: A Meta Analysis - Rafi Alfian Razan; Nur Aisiyah Widjaja; Anggie Lorenza; Vianca Samara Andhary; Naoval Diza Ananda (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Phenylketonuria (PKU) is one of the most common types of inborn error of metabolism. Low-phenylalanine diet has been the main treatment for children with PKU. However, recent therapeutic alternatives have emerged as a solution in children with PKU in the form of tetrahydrobiopterin (BH4). This meta analysis aims to assess the effectiveness of BH4 in terms of response rate, metabolic profile and growth status. Methods: Meta analysis was conducted by searching databases such as PubMed, ScienceDirect, Cochrane Library, medRxiv, and Scopus based on the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) guidelines. Data synthesis and analyses were conducted using R version 4.5.1 (R Foundation for Statistical Computing). Result: Fifteen studies were involved in this research, consisting of 1280 children (1063 given BH4). Eight studies reported BH4 reduced plasma phenylalanine concentration by around (686.83 mg/day [95% CI 394.85 to 978.82], p <0.001). Additionally, two studies reported a reduction in plasma phenylalanine concentration, measured in mg/kg/day, following BH4 administration. Children given BH4 and low phenylalanine diet combination showed a higher response rate compared to BH4 only (100% vs 76%). Two studies showed no difference in growth outcomes, which remained within the normal range. Conclusion: BH4 shows promise as an adjunct therapy for children with PKU, but confirmation through larger, standardized, long-term studies assessing outcomes such as growth status and long-term neurocognitive outcome is needed.